Insights into the Emerging Therapeutic Targets of Triple-negative Breast Cancer - Varshini, Magham Sai; Krishnamurthy, Praveen Thaggikuppe; Reddy, Ramakamma Aishwarya; Wadhwani, Ashish; Chandrashekar, V.M. (Current Cancer Drug Targets, 2025)
Triple-negative Breast Cancer (TNBC), the most aggressive breast cancer subtype, is characterized by the non-appearance of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2). Clinically, TNBC is marked by its low survival rate, poor therapeutic outcomes, high aggressiveness, and lack of targeted therapies. Over the past few decades, many clinical trials have been ongoing for targeted therapies in TNBC. Although some classes, such as Poly (ADP Ribose) Polymerase (PARP) inhibitors and immunotherapies, have shown positive therapeutic outcomes, however, clinical effects are not much satisfiable. Moreover, the development of drug resistance is the major pattern observed in many targeted monotherapies. The heterogeneity of TNBC might be the cause for limited clinical benefits. Hence,, there is a need for the potential identification of new therapeutic targets to address the above limitations. In this context, some novel targets that can address the above-mentioned concerns are emerging in the era of TNBC therapy, which include Hypoxia Inducible Factor (HIF-1α), Matrix Metalloproteinase 9 (MMP-9), Tumour Necrosis Factor-α (TNF-α), β-Adrenergic Receptor (β-AR), Voltage Gated Sodium Channels (VGSCs), and Cell Cycle Regulators. Currently, we summarize the ongoing clinical trials and discuss the novel therapeutic targets in the management of TNBC.
Keywords: tumour necrosis factor-α